Innovation methods of optimization of bone regeneration: platelet-rich plasma (literature review) (part 1) - Korzh, Mykola; Vorontsov, Petro; Vishnyakova, Iryna; Samoilova, Kateryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The issues of bone regeneration remain relevant even with the active development of biotechnology. The use of platelet-rich plasma to optimize osteoporosis is one of the promising directions in modern medicine. Objective: to performa comparative analysis, to generalize and systematize the results of studies on the classification, methods of obtaining and the possibility of using plasma-enriched platelets in animal experiments, and also in clinical conditions. Methods: publications over the past 20 years have been analyzed from the electronic databases of PubMed, Medline, abstracts, articles, abstracts, dissertations and other relational sources of scientific and medical information. Over 200 works have been found. Results: based on the information collected, the following issues were highlighted: receiving and classifying platelet-rich plasma, studying the effect of platelet-rich plasma on cells in vitro, and the possibility of combining platelet-rich plasma with biomaterials in animal experiments. In addition, the possibility of using platelet-rich plasma to restore bone tissue in a clinic in vivo is considered. It has been established that the use of platelet-rich plasma is one of the most promising modern methods for optimizing bone regeneration. The safety, efficacy and cost-effectiveness of platelet-rich plasma use are well documented in scientific literature. However, the main disadvantage of platelet-rich plasma is insufficient strength characteristics, which is a very important parameter for using it to fill bone defects, especially of critical size, in the case of osteotomy and surgical treatment of cancer. In this regard, the combination of platelet-rich plasma with osteoplastic materials, mesenchymal cells and growth factors is of particular interest. However, there are many controversial issues that require additional studies to create a transplant with properties that are as close as possible to the biological characteristics of the bone.